Osteopontin impairs host defense during established gram-negative sepsis caused by Burkholderia pseudomallei (melioidosis) - Van Der Windt, G; Wiersinga, W; Wieland, C; Tjia, I; Day, N; Peacock, S; Florquin, S; Van Der Poll, T (Public Library of Science, 2010)
BACKGROUND: Melioidosis, caused by infection with Burkholderia (B.) pseudomallei, is a severe illness that is endemic in Southeast Asia. Osteopontin (OPN) is a phosphorylated glycoprotein that is involved in several immune responses including induction of T-helper 1 cytokines and recruitment of inflammatory cells. METHODOLOGY AND PRINCIPAL FINDINGS: OPN levels were determined in plasma from 33 melioidosis patients and 31 healthy controls, and in wild-type (WT) mice intranasally infected with B. pseudomallei. OPN function was studied in experimental murine melioidosis using WT and OPN knockout (KO) mice. Plasma OPN levels were elevated in patients with severe melioidosis, even more so in patients who went on to die. In patients who recovered plasma OPN concentrations had decreased after treatment. In experimental melioidosis in mice plasma and pulmonary OPN levels were also increased. Whereas WT and OPN KO mice were indistinguishable during the first 24 hours after infection, after 72 hours OPN KO mice demonstrated reduced bacterial numbers in their lungs, diminished pulmonary tissue injury, especially due to less necrosis, and decreased neutrophil infiltration. Moreover, OPN KO mice displayed a delayed mortality as compared to WT mice. OPN deficiency did not influence the induction of proinflammatory cytokines. CONCLUSIONS: These data suggest that sustained production of OPN impairs host defense during established septic melioidosis.